Penyelesaian Sengketa Tanah PT. Balai Kayang Mandiri Dengan Masyarakat Di Kabupaten Siak - Kurniawan, T.Agung; ', Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Land is a gift from God. And as an important natural resource for humankind, it is no wonder the land becomes a special asset that does not stop triggering disputes. Land parcels that occur in Indonesia are usually disputes over ulayat rights, land grabs, and property rights disputes generally disputes that occur in Indonesia are resolved Mediation mediation is one part of alternative dispute resolution outside the courtThe purpose of this research is to find out why the dispute of PT. Balai Kayang Mandiri with the Community and how the parties must carry out the effort to complete the trialThe type of this research is sociological law research, because in this study the author directly conduct research in the area of the occurrence of the dispute this research was conducted in Siak regency, while the population and the sample are all parties related to the problems studied in this study data sources used, data primary, secondary data and tertiary data. Data collection techniques in this study with interviews and literature studiesDispute resolution of PT. Balai Kayang Mandiri with Community in Siak Regency there are some obstacles that each party disputes insist that the land that become dispute is an area of their own landKeywords: Dispute Resolution, PT. Balai Kayang Mandiri, Masyarakat.